The Influence of Historical Context on the Works of the Romantic Poets - SESHAGIRI, H.; Sai Krishna, Kota (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the profound influence of historical context on the works of Romantic poets, focusing on how major events such as the French Revolution, the Industrial Revolution, and the Napoleonic Wars shaped the themes, ideologies, and styles of their poetry. Romanticism emerged as a reaction to the Enlightenment’s rationalism and the socio-political upheavals of the late 18th and early 19th centuries, emphasizing individualism, imagination, and a deep connection to nature. Through an analysis of key poets such as William Wordsworth, Percy Bysshe Shelley, Lord Byron, and others, this study highlights how their works reflect the tensions of their era—ranging from revolutionary optimism to disillusionment, critiques of industrialization, and explorations of liberty and national identity. The intersection of historical events and poetic expression reveals the Romantic poets’ dual role as both chroniclers and critics of their time.